Monocytes of newly diagnosed juvenile DM1 patients are prone to differentiate into regulatory IL-10+ M2 macrophages - Juhas, Ulana; Ryba-Stanisławowska, Monika; Brandt-Varma, Agnieszka; Myśliwiec, Małgorzata; Myśliwska, Jolanta (Immunologic research, 2019)
Alternatively activated macrophages (M2) exert anti-inflammatory effects and are crucial for keeping balance between protective and destructive cell-mediated immunity in healing phase of inflammation. Two members of the interferon regulatory factors family, IRF5 and IRF4, are known to promote M1 or M2 phenotype, respectively. Our study aimed to analyse the effectiveness of the M2 differentiation process in vitro (achieved by IL-4 stimulation) and its relationship to the stage of type 1 diabetes mellitus (DM1) in juvenile patients. To identify the basic changes in M2 phenotype, we examined the expression of the surface CD206, CD14, CD86 molecules, intracellular IRF4 and IRF5 transcription factors as well as IL-10 and TNFα intracellular production. Ten newly diagnosed (ND-DM1) and ten long-standing (LS-DM1) patients were enrolled into the study. The control group consisted of six children. We observed a significantly higher number of unpolarised CD206 + CD14 + cells in the M2 cultures of DM1 subjects when compared to healthy ones. Examined cells presented common features with M1 macrophages (high levels of the CD14/CD86/IRF5 markers); however, they were weak TNFα producers in ND-DM1 patients. For the first time, we have revealed dysregulated IRF4/IRF5 axis in the analysed subpopulation derived from diabetic patients. Additionally, monocytes of ND-DM1 children were still able to differentiate into regulatory IL-10 + M2 macrophages, while this process was highly limited in LS-DM1 patients. Summarising, we suggest that the M2 polarisation process is less effective in DM1 patients than in healthy subjects and it may vary depending on the stage of disease. It can be concluded that in vitro differentiated M2 macrophages may be used in the future as inflammatory inhibitors for adoptive therapy experiments in ND-DM1 subjects.